GOVERNANCE OF LEBAK REGENCY GOVERNMENT IN PROMOTING SUSTAINABLE FOOD SECURITY BASED ON LOCAL WISDOM AMONG THE KASEPUHAN CITOREK INDIGENOUS COMMUNITY - Yustika Siti Mukaromah; Ida Widianingsih; Rd Ahmad Buchari (DIA: Jurnal Administrasi Publik, 2026)
Food security is a critical agenda in sustainable development. However, Lebak Regency faces declining rice productivity due to limited land, restricted access to fertilizers, and pest attacks. The indigenous Kasepuhan Citorek community maintains a food system based on local wisdom, including traditional agriculture, shifting cultivation, customary rice fields, and leuit (rice barns) as food reserves, which support social, cultural, and ecological sustainability. This study analyzes the governance of Lebak Regency in promoting food security based on local wisdom through policies, institutional support, and synergy with traditional practices. A qualitative descriptive approach was employed, with data collected through in-depth interviews, field observations, documentation, and literature review, and analyzed using Miles and Huberman’s interactive model. The findings indicate that the local government has strategic regulations and institutional programs, yet implementation is limited by institutional capacity, coordination challenges, and rule–implementation gaps. Synergy between the government and indigenous communities through participatory approaches strengthens food security by integrating traditional practices with modern interventions. The success of food security based on local wisdom depends on sustained collaboration and harmonization between formal policies and customary practices.